Why do proteases mess up with antigen presentation by re-shuffling antigen sequences?. (June 2018) - Liepe, Juliane; Ovaa, Huib; Mishto, Michele
Highlights: Non-canonical epitopes have emerged as large part of immunopeptidomes. Spliced peptides represent 20–30% of the MHC-I immunopeptidome variety. Peptide splicing by proteasome and other proteases is regulated and efficient. Peptide splicing efficiency can have implications in defining the immunological self. Abstract : The sequence of a large number of MHC-presented epitopes is not present as such in the original antigen because it has been re-shuffled by the proteasome or other proteases. Why do proteases throw a spanner in the works of our model of antigen tagging and immune recognition? We describe in this review what we know about the immunological relevance of post-translationally spliced epitopes and why proteases seem to have a second (dark) personality, which is keen to create new peptide bonds.